2007
DOI: 10.1093/nar/gkm477
|View full text |Cite
|
Sign up to set email alerts
|

Delta Notch and then? Protein interactions and proposed modes of repression by Hes and Hey bHLH factors

Abstract: Hes and Hey genes are the mammalian counterparts of the Hairy and Enhancer-of-split type of genes in Drosophila and they represent the primary targets of the Delta–Notch signaling pathway. Hairy-related factors control multiple steps of embryonic development and misregulation is associated with various defects. Hes and Hey genes (also called Hesr, Chf, Hrt, Herp or gridlock) encode transcriptional regulators of the basic helix-loop-helix class that mainly act as repressors. The molecular details of how Hes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
325
0
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(351 citation statements)
references
References 162 publications
13
325
0
13
Order By: Relevance
“…However hepatic transcription of another Notch target, the transcription factor Hes1 , which has been implicated in the regulation of hepatic lipid metabolism and fatty liver disease (FLD), was unchanged (data not shown) [41]. The levels of mRNAs encoding the Hes1 related genes Hes5 , Hey1 and Hey2 were also unchanged by ICD-E expression, as were Sox9 and Hnf1β (data not shown) [22], [42]. In contrast to the liver, strong induction of Hes5 follows expression of ICD-E in the intestine [20].…”
Section: Resultsmentioning
confidence: 99%
“…However hepatic transcription of another Notch target, the transcription factor Hes1 , which has been implicated in the regulation of hepatic lipid metabolism and fatty liver disease (FLD), was unchanged (data not shown) [41]. The levels of mRNAs encoding the Hes1 related genes Hes5 , Hey1 and Hey2 were also unchanged by ICD-E expression, as were Sox9 and Hnf1β (data not shown) [22], [42]. In contrast to the liver, strong induction of Hes5 follows expression of ICD-E in the intestine [20].…”
Section: Resultsmentioning
confidence: 99%
“…The hairy/enhancer of split (Hes) genes are highly conserved proteins that are regulated by Notch in multiple cell types, reviewed in [7,8]. Hairy/Enhancer of split family genes were first described as neurogenic genes in Drosophila (like Notch, Deltex and Mastermind), since embryos lacking the function of these genes showed an increased number of neuroblasts at the expense of epidermal precursors, reviewed in [2,9].…”
Section: Notch Target Genesmentioning
confidence: 99%
“…Several lines of evidence have suggested that these genes are indeed direct Notch target genes: a) The promoters of Hes1, Hes5 and Hes7 as well as Hey1, Hey2 and HeyL (subfamily of Hes, related with YRPW motif) can be activated by a constitutive active form of Notch1 [10 -12], reviewed in [7]; constitutive active Notch describes a mutant of Notch that is continuously proteolytically processed and migrating to the nucleus, b) endogenous Hey1 and Hey2 show an upregulation by NICD in several different cell lines [13], c) in co-culture experiments with Notch-ligand expressing cells, that achieve a more physiological level of Notch signaling, these genes are upregulated as well [13 -15]; these experiments were also performed in the presence of cyclohexamide, an inhibitor of protein synthesis, to exclude secondary effects, d) k-secretase inhibitor DAPT, which prevents cleavage of Notch, was added to Tcell leukemia cell lines which show constitutive-active Notch signaling; subsequent microarray analysis identified again members of this transcription factor family as direct Notch target genes [16]. Therefore, in mammals, the best-described Notch target genes are indeed the transcription factors Hes1, Hes5 and Hey1 [8,17]. Hes and Hey proteins are helix-loop-helix transcription factors that function as transcriptional repressors.…”
Section: Notch Target Genesmentioning
confidence: 99%
“…The WRPW domain, located at the C-terminal end, is essential for the repressor activity via recruitment of the co-repressor Transducin-like E(spl) (TLE1-4)/ Groucho-related gene (Grg), a homologue of Drosophila Groucho. The Hey family factors contain a YRPW (Tyr-Arg-Pro-Trp) motif instead of the WRPW motif, which contributes to the weaker binding of Hey factors to TLE than the Hes factors (Iso et al, 2001;Fischer & Gessler, 2007).…”
Section: Hes Family Members and Protein Structuresmentioning
confidence: 99%